2022
DOI: 10.3389/fendo.2022.904237
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Levels With the Prevalence of Hypertension in Chinese Women: A Cross-Sectional Study Based on 32 Health Check Centers

Abstract: BackgroundDyslipidemia is strongly associated with the development of hypertension. In our previous study, it was shown that elevated TC, LDL-c, and non-HDL-c were associated with the prevalence of hypertension in Chinese men, whereas the relationship between HDL-c and hypertension shifted from no association to a positive association after adjusting for the BMI. To further accumulate epidemiological evidence in Asian women, this study aimed to investigate the relationship between lipid profile and prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Based on the research conducted by Deng et al, elevated TC, LDL-C, and non-HDL-C can potentially lead to hypertension by elevating the levels of circulating endothelin-1. As a result, there was an inverse association between HDL-C and the incidence of hypertension [ 39 ]. Nakajima et al reported an inverted J-shaped association between HDL-C and hypertension risk (≥ 140/90 mm Hg) in both sexes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the research conducted by Deng et al, elevated TC, LDL-C, and non-HDL-C can potentially lead to hypertension by elevating the levels of circulating endothelin-1. As a result, there was an inverse association between HDL-C and the incidence of hypertension [ 39 ]. Nakajima et al reported an inverted J-shaped association between HDL-C and hypertension risk (≥ 140/90 mm Hg) in both sexes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2022) examined the impact of these dietary patterns on blood lipids across seven ethnic groups, revealing that MedDiet and DASH diet were negatively associated with blood lipids [138]. Additionally, several studies have elucidated the close relationship between lipid profile and hypertension [139][140][141]. Similarly, a study on the Iranian population compared adherence to the DASH diet and MedDiet with blood lipid levels, demonstrating that high adherence to the MedDiet was associated with lower odds of LDL/HDL, which could indirectly influence blood pressure regulation [142].…”
Section: Meddiet and Dashmentioning
confidence: 99%